2021
DOI: 10.1002/onco.13753
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Genomic Characterization of PD-L1 Positive Urothelial Carcinomas

Abstract: Introduction. Pembrolizumab was approved with an accompanying companion diagnostic (CDx) assay (PD-L1 DAKO 22C3) for urothelial carcinoma (UC). In this study, we further characterize the clinicopathologic and genomic features of UC that are PD-L1 positive. Materials and Methods. The cohort of this study consisted of a total of 528 consecutive UC patients with PD-L1 IHC and comprehensive genomic profiling (CGP). All PD-L1 IHC testing was performed using the DAKO 22C3 CDx assay for UC. PD-L1 positivity was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…We found that 29% of primary tumors had a PD‐L1 CPS score of ≥10 ( i.e., positive PD‐L1 expression). This finding is in line with other studies based on the 22C3 antibody, in which 20–40% of UC tumors have a reported PD‐L1 CPS of ≥10 [14,15]. We found no difference in primary tumor PD‐L1 expression according to gender, and in line with one recent study nor according to stage or histological subtype [16].…”
Section: Discussionsupporting
confidence: 93%
“…We found that 29% of primary tumors had a PD‐L1 CPS score of ≥10 ( i.e., positive PD‐L1 expression). This finding is in line with other studies based on the 22C3 antibody, in which 20–40% of UC tumors have a reported PD‐L1 CPS of ≥10 [14,15]. We found no difference in primary tumor PD‐L1 expression according to gender, and in line with one recent study nor according to stage or histological subtype [16].…”
Section: Discussionsupporting
confidence: 93%
“…When available we counted on Italian cancer registries, like many others, do not extensively collect information on predictive bio-markers as PD-1/PD-L1, EGFR, ALK, or dMMr/MSI-H. Therefore, we had to use data from the literature [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (see Online Supplementary Materials) taking a chance of possible individual, tumor and technical variabilities. 41 ICI are usually authorized for advanced or metastatic cancers, therefore we used, according to US and China authors, [12][13][14] the number of cancer deaths provided by the Italian Institute of Statistics as a proxy of incident metastatic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Italian cancer registries, like many others, do not extensively collect information on predictive bio-markers as PD-1/PD-L1, EGFR, ALK, or dMMr/MSI-H. Therefore, we had to use data from the literature 22 - 38 (see Online Supplementary Materials ) taking a chance of possible individual, tumor and technical variabilities. 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations